Modulation of K(v)7 potassium channels by a novel opener pyrazolo[1,5-a]pyrimidin-7(4H)-one compound QO-58 - Zhang, F (Blackwell Publishing Ltd, 2013)
BACKGROUND AND PURPOSE: Modulation of K(v)7/M channel function represents a relatively new strategy to treat neuronal excitability disorders such as epilepsy and neuropathic pain. We designed and synthesized a novel series of pyrazolo[1,5-a] pyrimidin-7(4H)-one compounds, which activate K(v)7 channels. Here, we characterized the effects of the lead compound, QO-58, on K(v)7 channels and investigated its mechanism of action. EXPERIMENTAL APPROACH: A perforated whole-cell patch technique was used to record K(v)7 currents expressed in mammalian cell lines and M-type currents from rat dorsal root ganglion neurons. The effects of QO-58 in a rat model of neuropathic pain, chronic constriction injury (CCI) of the sciatic nerve, were also examined. KEY RESULTS: QO-58 increased the current amplitudes, shifted the voltage-dependent activation curve in a more negative direction and slowed the deactivation of K(v)7.2/K(v)7.3 currents. QO-58 activated K(v)7.1, K(v)7.2, K(v)7.4 and K(v)7.3/K(v)7.5 channels with a more selective effect on K(v)7.2 and K(v)7.4, but little effect on K(v)7.3. The mechanism of QO-58's activation of K(v)7 channels was clearly distinct from that used by retigabine. A chain of amino acids, Val(224)Val(225)Tyr(226), in K(v)7.2 was important for QO-58 activation of this channel. QO-58 enhanced native neuronal M currents, resulting in depression of evoked action potentials. QO-58 also elevated the pain threshold of neuropathic pain in the sciatic nerve CCI model. CONCLUSIONS AND IMPLICATIONS: The results indicate that QO-58 is a potent modulator of K(v)7 channels with a mechanism of action different from those of known K(v)7 openers. Hence, QO-58 shows potential as a treatment for diseases associated with neuronal hyperexcitability.